Studies On Growth Response, Feed Efficiency And Carcas Characteristics Of Pigs Reared Upto Different Market Weight On Two Dietary Treatments - Ramachandran P (Department of Nutrition, College of Veterinary and Animal Sciences, 1977)
A detailed investigation was carried out to study the growth rate, feed efficiency, carcass quality and economics of production of fattening pigs maintained on two dietary treatments differing in protein levels and reared upto three different body weights. Thirtysix weaner pigs of Large White Yorkshire breed belonging to the University Pig Breeding Farm, Mannuthy were distributed under two dietary treatments and divided into three groups 1, 11 and 111 of six animals each, the animals in the three groups being slaughtered at body weights of 55, 70 and 85 kg.respectively. Higher dietary protein level of 18 per cent promoted better weight gains in pigs during the initial period of their growth. Lowering of protein level in the finishing ration reduced the weight gain and feed efficiency of the animals. A dietary protein level of 16 per cent throughout the feeding period brought about linear increase in overall average daily gain at all body weights studied. Though the protein level does not seem to influence any of the carcass characteristics studied, the dressing percentage, carcass length, backfat thickness and eyemuscle area are positively correlated with body weights under both the dietary treatments. Fat constants are not affected either by protein levels or by live weights. The overall results obtained during the course of the present investigation indicate that the unit cost of production of fattening pigs is least at 55 kg live weight on the dietary treatment A having 18 – 16 – 14 per cent protein and at 85 kg live weight on the dietary treatment B having 16 per cent protein level throughout.